Quantitative market survey of non-woody plants sold at Kariakoo Market in Dar es Salaam, Tanzania. (10th August 2018) - Posthouwer, Chantal; Veldman, Sarina; Abihudi, Siri; Otieno, Joseph N.; van Andel, Tinde R.; de Boer, Hugo J.
Abstract: Ethnopharmacological relevance: In Tanzania, traditional medicine plays a significant role in health care and local economies based on the harvesting, trade and sale of medicinal plant products. The majority of this plant material is said to originate from wild sources, and both traditional healers and vendors are concerned about the increasing scarcity of certain species. Aim of the study: A market survey of non-powdered, non-woody medicinal plants was conducted at Kariakoo Market in Dar es Salaam, the major hub for medicinal plant trade in Tanzania, to assess sustainability of traded herbal medicine. Materials and Methods: For this study, fresh and dried herbs, seeds and fruits were collected and interviews were conducted to obtain information on vernacular names, preparation methods, monthly sales, uses and prices. Bundles of herbal medicine offered for sale were weighed and counted to calculate the value and volumes of daily stock at the market. Results: A total of 71 medicinal plant products belonging to 62–67 different species from at least 41 different plant families were identified. We identified 45 plant products to species level, 20 products to genus level and four to family level. Plant species most encountered at the market were Suregada zanzibariensis, Myrothamnus flabellifolia and Sclerocarya birrea . The major use categories reported by the vendors were ritual purposes, digestive disorders and women's health. Annual sales are estimated to be in excess of 30 t and close to 200, 000 USD, and trade in herbal medicine at Kariakoo Market provides subsistence income to many local vendors. Conclusions: A large diversity of wild-harvested plant species is traded as medicinal products in Tanzania, including species listed on CITES Appendices. Identifying and monitoring temporal changes in availability per season and from year to year will reveal which species are most affected by this trade, and help relevant authorities in Tanzania to find alternative sources of income for dependent stakeholders and initiate targeted efforts to protect threatened plant species. Graphical abstract: